2020
DOI: 10.3389/fimmu.2019.03050
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Inflammatory Response to Intracellular Bacterial c-di-AMP

Abstract: Cyclic-di-AMP (c-di-AMP) is a bacterial second messenger that is produced by intracellular bacterial pathogens in mammalian host macrophages. Previous reports have shown that c-di-AMP is recognized by intracellular pattern recognition receptors of the innate immune system and stimulate type I interferon response. Here we report that the response to c-di-AMP includes a post-transcriptional component that is involved in the induction of additional inflammatory cytokines including IL-6, CXCL2, CCL3, and CCL4. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Interestingly, Giardia infection up-regulates several downstream RIG-I signaling pathway genes during the infection ( Table S2 ), such as TRAF3, IKK, and TBK1. Furthermore, pathogenic bacteria can also manipulate TTP levels via the bacterial secondary messenger cyclic-di-AMP (c-di-AMP) ( Mahmoud et al., 2020 ). Thus, up-regulation of TTP might be a general immunosuppressive mechanism used by pathogenic microbes to suppress an initial up-regulation of inflammatory mediators and this can be studied further in the Giardia -Caco-2 system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Giardia infection up-regulates several downstream RIG-I signaling pathway genes during the infection ( Table S2 ), such as TRAF3, IKK, and TBK1. Furthermore, pathogenic bacteria can also manipulate TTP levels via the bacterial secondary messenger cyclic-di-AMP (c-di-AMP) ( Mahmoud et al., 2020 ). Thus, up-regulation of TTP might be a general immunosuppressive mechanism used by pathogenic microbes to suppress an initial up-regulation of inflammatory mediators and this can be studied further in the Giardia -Caco-2 system.…”
Section: Discussionmentioning
confidence: 99%
“…Trained monocytes and macrophages display functional and epigenetic reprogramming, leading to increased production of cytokines and chemokines, which are viewed as primary indicators of trained immunity ( 37 ), and improved phagocytosis and killing capacity ( 51 , 52 ). c-di-AMP has been identified to be a potent inducer of several proinflammatory cytokines and chemokines such as IL-1β, IL-6, and TNF-α in macrophages ( 27 , 31 , 32 , 53 ). These proinflammatory cytokines are also considered as mediators of trained immunity ( 8 , 9 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Released type I IFN can bind to the IFN receptor, activating STATs (signal transducer and activator of transcription), mitogen-activated protein kinase (MAPK), and phosphatidylinositol 3-kinase (PI3K) signal pathways, regulating various physiological activities and initiating anti-pathogen responses. Mahmoud et al (2019) demonstrated that c-di-AMP could specifically enhance the expression of additional inflammatory cytokines, namely, IL-6, CXCL2, CCL3, and CCL4, the mRNAs of which contain AU-rich elements (AREs) in the 3′ UTR that promote decay and repress translation. c-di-AMP was able to promote the phosphorylation of p38 MAPK as well as the induction of the ARE-binding protein TTP, both of which are components of a signaling pathway that modulate the expression of ARE-containing mRNAs at the post-transcriptional level.…”
Section: Cyclic Di-adenosine Monophosphate Modulates Host Innate Immu...mentioning
confidence: 99%
“…c-di-AMP was able to promote the phosphorylation of p38 MAPK as well as the induction of the ARE-binding protein TTP, both of which are components of a signaling pathway that modulate the expression of ARE-containing mRNAs at the post-transcriptional level. Pharmacological inhibition of p38 reduced the c-di-AMP-dependent release of induced cytokines, while TTP knockdown increased their release and mRNA stability ( Mahmoud et al, 2019 ). These data propose that c-di-AMP can activate the p38 MAPK pathway via a post-transcriptional regulatory effect and subsequently enhance the expression of inflammatory cytokines.…”
Section: Cyclic Di-adenosine Monophosphate Modulates Host Innate Immu...mentioning
confidence: 99%